1990
DOI: 10.1042/bj2710365
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes-induced alterations in the expression, functioning and phosphorylation state of the inhibitory guanine nucleotide regulatory protein Gi-2 in hepatocytes

Abstract: Levels of the G-protein alpha-subunits alpha-Gi-2, alpha-Gi-3 and the 42 kDa, form of alpha-Gs were markedly decreased in hepatocyte membranes from streptozotocin-diabetic animals as compared with normals. In contrast, no detectable changes in alpha-Gi subunits were seen in liver plasma membranes of streptozotocin-diabetic animals, although levels of the 45 kDa form of Gs were increased. G-protein beta subunits in plasma membranes were unaffected by diabetes induction. Analysis of whole-liver RNA indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(56 citation statements)
references
References 42 publications
4
52
0
Order By: Relevance
“…In hepatocytes of streptozotocin-induced diabetic rats [25,26] there is a loss of Gi function which appears to result from both a reduction in the expression of Gi-2 and also its increased phosphorylation by protein kinase C. Treatment of a variety of different cell types with tumour promoting phorbol esters has been shown to lead to the loss of guanine nucleotide-elicited, G~-mediated inhibition of adenylate cyclase activity [13,37]. Similar observations of crippled G~ function have also been seen in cells challenged with ligands which stimulate phospholipid metabolism or with DAG [13], suggesting that it is the activation of protein kinase C which provides the molecular basis of this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In hepatocytes of streptozotocin-induced diabetic rats [25,26] there is a loss of Gi function which appears to result from both a reduction in the expression of Gi-2 and also its increased phosphorylation by protein kinase C. Treatment of a variety of different cell types with tumour promoting phorbol esters has been shown to lead to the loss of guanine nucleotide-elicited, G~-mediated inhibition of adenylate cyclase activity [13,37]. Similar observations of crippled G~ function have also been seen in cells challenged with ligands which stimulate phospholipid metabolism or with DAG [13], suggesting that it is the activation of protein kinase C which provides the molecular basis of this phenomenon.…”
Section: Resultsmentioning
confidence: 99%
“…As well as this, activation of protein kinase C also causes the loss of 'tonic' GTP-mediated inhibition of adenylyl cyclase through Gi [17]. This apparently physiological 'crosstalk' mechanism appears, however, to be inappropriately activated in streptozotocin-induced diabetes [25,26] where we have noted the loss of such 'tonic' GTP-elicited inhibition of adenylyl cyclase [25,26]. This appears to be due in part to the reduced expression of the inhibitory G-protein ~-Gi-2 but also to the increased phosphorylation, through the action of PKC, of ~-Gi-2 itself [18,26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another line of evidence comes from the altered function of Gi in diabetes, where abolished effects of insulin on Grlike proteins have been documented [33]. It has also been reported that the Gi function is impaired in liver membranes of animals with experimentally induced diabetes [34][35][36][37]. These suggest that some metabolic effects of insR may be mediated by Grlike proteins.…”
Section: Resultsmentioning
confidence: 94%
“…G i α2, but not G i α3 from hepatocytes, was found to be phosphorylated on serine residues by protein kinase C both in i o and in itro [37][38][39]. Elevated phosphorylation of G i α2 was correlated with decreased ability to inhibit adenylate cyclase [40,41]. Tyrosine phosphorylation of G q α [42], G s α [43] and functional consequences have also been reported.…”
Section: Discussionmentioning
confidence: 99%